Identification And Characterisation Of Enoyl-Coa Hydratases (Phaj/Maoc) From Non-Mcl Pha Accumulating Bacteria For The Production Of P(3hb-Co-3hhx) Copolymer In Transformant Strains - Jia Hui, Wan (2024)
Polyhydroxyalkanoate (PHA) is a biodegradable plastic produced naturally by microorganisms, where it serves as carbon storage and is completely biodegradable in the natural environment. There are two types of PHA, which are short-chain-length PHA (SCL-PHA), consisting of monomers with 3 to 5 carbons, and medium-chain-length PHA (MCL-PHA), consisting of monomers with 6 to 14 carbons. The poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] [P(3HB-co-3HHx)] copolymer is composed of both SCL- and MCL-PHA, which has a close resemblance to some conventional plastics and displays promising potential as a substitute for non-biodegradable plastics such as single-use plastic. Enoyl-CoA hydratases (PhaJ/MaoC) are the enzymes essential in the β-oxidation cycle of fatty acid metabolism that can increase the supply of 3HHx monomer compositions in the production of the copolymer. The properties of the copolymer may be altered by varying the 3HHx molar composition. To date, there is a lack of effective enoyl-CoA that can increase the supply of 3HHx monomer to produce P(3HB-co-3HHx); therefore, this study aims to identify and characterise more effective enoyl-CoA hydratases to overcome this problem. In this study, the bioinformatic analysis was done to screen for functional PhaJs or MaoCs from non-MCL-PHA accumulating bacteria such as Burkholderia sp. USM, Jeongeupia sp.